2022
DOI: 10.1002/cptc.202200062
|View full text |Cite
|
Sign up to set email alerts
|

Benzodithiophene‐Based, Donor–Acceptor–π–Donor–Acceptor Systems as Hole Transporting Materials for Efficient Perovskite Solar Cells

Abstract: Four new donor-acceptor-π-bridge-accepter-donor hole-transporting materials (HTMs) were developed based on the 2,2'-(4,8-bis(octyloxy)benzo [1,2-b:4,5-b']dithiophene (OBDT) core moiety functionalised with two diphenylamine-based donor units as outlying moieties. The compounds were designed, synthesised and used in perovskite solar cells (PSCs). Each HTM was thoroughly characterized with various spectroscopic techniques, and the surface and cross-sectional morphologies of the thin-film topmost layer, steady-sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 60 publications
(117 reference statements)
0
2
0
Order By: Relevance
“…[15][16][17][18] Thus, S. Pola et al showed recently that BDT-based small molecules with a DA-p-AD structure (donor-acceptor-p-bridge-acceptor-donor, where the p-bridge is a BDT derivative) are promising HTMs for PSCs. 19 Combination of BDT with indole derivatives in DA-p-AD HTMs allowed a high PCE of 19% to be achieved along with the good stability of devices. The group led by Y. Li constructed PSCs with outstanding PCEs of 23-24% by using symmetric or more complex asymmetric DA-p-AD HTMs, where the p-bridge was represented by a uorine-substituted BDT moiety.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18] Thus, S. Pola et al showed recently that BDT-based small molecules with a DA-p-AD structure (donor-acceptor-p-bridge-acceptor-donor, where the p-bridge is a BDT derivative) are promising HTMs for PSCs. 19 Combination of BDT with indole derivatives in DA-p-AD HTMs allowed a high PCE of 19% to be achieved along with the good stability of devices. The group led by Y. Li constructed PSCs with outstanding PCEs of 23-24% by using symmetric or more complex asymmetric DA-p-AD HTMs, where the p-bridge was represented by a uorine-substituted BDT moiety.…”
Section: Introductionmentioning
confidence: 99%
“…KEYWORDS intramolecular charge transfer, donor-acceptor systems, fluorosolvatochromism, photophysical properties, theoretical calculations Introduction Push-pull structures are conjugated organic molecules integrated by electron-donating and electron-withdrawing moieties separated by a π-system, which broadens the charge distribution across the molecule, endowing it with exotic optical and electronic properties (Bureš, 2014). This class of materials has been extensively used as sensitizers in dye-sensitized solar cells (DSSCs) (Verbitskiy et al, 2014;Verbitskiy et al, 2015;Tan et al, 2016;Kozlov et al, 2017;Sun et al, 2018;Verbitskiy et al, 2021b) and hole-transporting materials in perovskite-based solar cells (Maddala et al, 2021;Bouihi et al, 2022;Manda et al, 2022) owing to their high molar absorption coefficient and efficient hole mobility, respectively. Moreover, they can be integrated into organic light-emitting diodes (OLEDs) (Wong et al, 2002;Wu et al, 2002;Nakao et al, 2017;Ryutaro et al, 2018;Verbitskiy et al, 2021a) because of their high fluorescence quantum yields (Φ F ).…”
mentioning
confidence: 99%